The Influence Of Work Ability, Work Compensation, And Work Supervision On Employee Performance At PT. Pembangunan Prasarana Sumatera Utara - Nadya, Dea; Wulandari, Niken; Juniarti, Juniarti (Jurnal Fokus Manajemen, 2025)
This study ains to analyze how much influence work ability, work compensation, and work supervision have on employee performance at PT. Pembangunan Prasarana Sumatera Utara. Quantitative methods based on an associative approach were used in this investigation. All 55 workers of PT. Pembangunan Prasarana Sumatera Utara made up the population in this research. Multiple linear regression was utilized for data analysis, and saturation sampling was employed to choose the sample. It is evident from the estimated t value < t table (1.519 < 2.006) and a significant level of 0.135 > 0.05 that work ability does not impact performance, according to the findings of this research. According to the study's indicate that work compensation effects performance, this can be seen from the calculated t value> t table (5.321 < 2.006) and a significance level of 0.000 < 0.05, job remuneration does not effect performance. As the computed t value > t table (3.182 < 2.006) and a significant level of 0.002 < 0.05 show, the study's findings suggest that job supervision influences performance. Based on the estimated f value (54.637 > 2.78), a significant level of 0.000 < 0.05, and the fact that work ability, work compensation, and work supervision all impact employee performance at the same time, it is clear that these factors influence performance in this research.